PENGARUH INSENTIF, SIKAP, KESADARAN, PENGETAHUAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WPOP UMKM KABUPATEN TULUNGAGUNG - Yustika, Nadila Aprilia; Nurdiwati, Diah; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2023)
Testing of tax incentive variables, attitudes, awareness, knowledge and tax sanctions to determine their effect on MSME WPOP compliance in Tulungagung Regency. This research uses 100 MSME actors who registered with the Cooperatives and Micro Enterprises Office of Tulungagung Regency in 2022. Causal quantitative techniques were chosen as analytical tools by collecting data using questionnaires and using statistical tools SPSS version 27 to analyze data with multiple linear analysis. The results of this study show that (1) Tax incentives have a partial effect on MSME WPOP compliance. (2) Attitude does not have a partial effect on MSME WPOP compliance. (3) Awareness does not have a partial effect on MSME WPOP compliance. (4) Knowledge has a partial effect on MSME wpop compliance. (5) Tax sanctions do not have a partial effect on MSME WPOP compliance.